Epidemiological, Clinical, Microbiological, and Risk Factors of Pyogenic Liver Abscess: An 18-years Retrospective Single-Center Analysis - Mina Fransawy Alkomos; Elias Estifan; Gabriel Melki; Sami Adib; Walid Baddoura (Greater Baltimore Medical Center, 2021)
Background: A pyogenic liver abscess (PLA) is the most frequently observed subtype of liver abscess in the western world. The disease has been subjected to a remarkable change. We aimed to investigate the recent trend in pyogenic liver abscess's epidemiology, clinical, microbiological, and risk factors features.Methods: A retrospective analysis of medical records was done for the patients diagnosed with PLA from January 2000 to June 2018. The institutional review board approved the study.Results: We identified 113 patients with PLA, 60% were males, with a mean age of 54 ± 20 years, and 58 ± 19 years old for males and females, respectively (p = 0.298), with an increasing annual incidence in 2012-2013, and 2016-2017 (Figure 1). Fever and right upper quadrant abdominal pain were the most common symptoms (65%, 55%, respectively). Forty percent of the patients had Biliary tract diseases like cholecystitis or biliary intervention as cholecystectomy or ERCP, and 20% had diabetes mellitus (Table 1). The abscess culture was obtained in 96 cases, 37 cases were negative (39%), 27 cases showed polymicrobial growth (28%) and 15 cases showed Escherichia coli (16%) (Figure 2). The abscess cultures were mostly negative in the first 5 years, then changed to Streptococcus anginosus, and polymicrobial growth in the last four years.Conclusions: PLA is more common in males with a recent increase in incidence. Culture negative PLA was observed in patients who were empirically treated with antibiotics. Polymicrobial was the most common identifiable organism with a change in the microbiological trend every 5 years.